The Absence of Love and Hopes of Shion Uzuki in The Xenosaga Trilogy - Levina Djajadi; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2013)
Among video games, The Xenosaga Trilogy is widely recognized due to its complex storyline. The psychological struggle of the main character, Shion Uzuki, is one of the aspects that drives the story from the beginning up to its conclusion. Despite her seemingly bright personality, Shion has an absence of love and hopes, as she lives her life monotonously without any set goal. It later leads her to develop a strong attachment to KOS-MOS, an android. As such, in this study, we want to analyze the reasons Shion has the absence of love and hopes in the first place and the ways she struggles to recover from that absence. In order to answer these questions, we use 3 psychological theories, namely Post-Traumatic Stress Disorder (PTSD), Transference, and Countertransference. We find out that Shion’s absence of love and hopes is apparently caused by her traumatic past and her PTSD. As a unconscious response to this, Shion tries to recover by using transference. This attempt fails, but Shion is finally healed thanks to KOS-MOS’ countertransference. In conclusion, Shion fully recovers from her traumatic past and PTSD because of KOS-MOS’ countertransference instead of her own transference.